STRATEGI GURU DALAM MENANAMKAN SIKAP TOLERANSI SISWA - Titi Puspita Sari (YAYASAN CENDEKIA CITRA GEMILANG, 2024)
This research aims to describe the teacher's strategy in instilling an attitude of tolerance in students at SDN 37 Cakranegara and the supporting and inhibiting factors for teachers in instilling an attitude of tolerance in students at SDN 37 Cakranegara. This research uses a descriptive qualitative approach. This research was carried out at SDN 37 Cakranegara, Jl. Pancor, Babakan, District. Sandubaya, Mataram City. Data sources from teachers and students. The data collection techniques used were observation, interviews, and documentation. The data analysis techniques in this research are data collection, data reduction, data presentation, and conclusion. Checking the validity of the data is done by extending observations, observing persistence, triangulation, coding, and sufficient references. Based on the research results, it was found that the teacher's strategy in instilling an attitude of tolerance in students is: (1) The teacher provides advice or motivation to students. (2) The teacher adjusts the students' sitting positions so that students can tolerate well in the classroom. (3) The teacher divides the imtaq places for Muslim and non-Muslim students. The supporting factors for teachers in instilling an attitude of tolerance in students are: (1) Student awareness and (2) School environment. The inhibiting factors for teachers in instilling an attitude of tolerance in students are (1) Student environment and (2) Bullying behavior from students.